1987
DOI: 10.1002/ijc.2910390616
|View full text |Cite
|
Sign up to set email alerts
|

Influence of some dietary chemopreventive agents on the expression of functional differentiation of the mouse mammary gland in vitro

Abstract: The purpose of the present studies was to determine the influence of the chemopreventive agents selenium, 4-(hydroxyphenyl)-retinamide (4-HPR) and beta-carotene, on functional differentiation (lactogenesis) of the mouse mammary gland cells. The hormone-induced expression of the milk-protein genes, beta-casein, epsilon-casein and the whey acidic protein (WAP) was used as molecular marker of differentiation of the mammary cells in organ culture medium containing insulin, prolactin, aldosterone and hydrocortisone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…It has been reported that retinoids inhibit differentiation and proliferation in the mammary gland of experimental animal (168,169). Retinoic acid, but not retinyl acetate, can reverse the growth stimulation induced by ovarian hormones in lactating rat mammary gland in organ culture (19).…”
Section: Retinoidsmentioning
confidence: 98%
“…It has been reported that retinoids inhibit differentiation and proliferation in the mammary gland of experimental animal (168,169). Retinoic acid, but not retinyl acetate, can reverse the growth stimulation induced by ovarian hormones in lactating rat mammary gland in organ culture (19).…”
Section: Retinoidsmentioning
confidence: 98%
“…Vitamin A status is a possible factor contributing to the development of many human cancers, including those of the breast. Epidemiological studies, experiments with animal models and clinical trials have implicated vitamin A status as an important factor in the development of a variety of human cancers (1)(2)(3)(4)(5)(6). These studies establish a link between dietary retinoid intake and cancer risk, and further show that retinoids can prevent progression of some, but not all, human cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Seleniuminduced inhibition of RNA and DNA poly merases [65], alterations in protein phos phorylation [45] and cellular glutathione [57,58] as well as hypomethylation of DNA [66] and induction of differentiation [67,68] have been reported recently. The signifi cance of these observations with respect to inhibition of cell growth has not been well defined with the exception of the effects on DNA polymerases.…”
Section: Possible Mechanisms Of Selenium Actionmentioning
confidence: 99%